Palliative medicine specialists' causal explanations for depression in the palliative care setting: a qualitative in-depth interview study. Issue 2 (28th April 2014) - Ng, Felicity; Crawford, Gregory B; Chur-Hansen, Anna
Abstract : Objective: Medical practitioners have different causal explanations for depression, and may have greater difficulty in explaining causality of depression in the palliative care setting. The objective of this study was to investigate and describe the causal explanations of depression in the palliative care setting, from the perspective of palliative medicine specialists. Methods: Palliative medicine specialists practising in Australia were recruited and purposively sampled. Individual semistructured, in-depth interviews were conducted to explore their explanatory models of depression, including a focus on causal explanations. Nine participants were interviewed to reach data saturation. Interview transcripts were analysed for themes. Results: Six themes for causal explanations of depression were identified: (1) Depression is inexplicable; (2) Biological explanations—primarily neurotransmitter depletion; (3) Psychological explanations—including reaction to circumstances, inability to accept illness and dying, diminished self, and coping mechanisms; (4) Social explanations—including inadequate social support, and contribution from modern medicine and societal norms; (5) Interrelationships between causal factors—mainly multifactoriality; (6) Different explanation for de novo and pre-existing depressions. Participants also articulated a link between causal explanations and clinical interventions. Conclusions: Palliative medicine specialists hold causal explanations of depression that align with the biopsychosocial and vulnerability-stress models. They use multiple individual explanations with diverse theoretical underpinnings, and largely view depression as multifactorial in causality. Given that causal explanations are linked to clinical interventions, these findings have implications for clinical practice and medical education.